The genus Mustilizans Yang, 1995 (Lepidoptera: Endromidae) in India with the description of a new species - Chandra, Kailash; Singh, Navneet; Kumar, Vikas; Ranjan, Rahul; Gayen, Subrata; Das, Moumita; Dey, Rushati (Zootaxa, 2019)
A new species of the family Endromidae, Mustilizans zolotuhini sp. nov. is described from Dihang-Dibang Biosphere Reserve, Arunachal Pradesh, India. The subspecies, Mustilizans dierli refugialis Zolotuhin, 2007 is recorded for the first time from Sikkim, India. The distribution of the species known from India is mapped. The holotype of the new species is deposited in the Lepidoptera Section, National Zoological Collections, Zoological Survey of India, Kolkata.